Livelihood pattern of rural women garment workers at Dhaka city - Ali, RN; Begum, F; Salehin, MM; Farid, KS (Journal of the Bangladesh Agricultural University, 2010)
The study was an attempt to analyse the economic, social and health conditions of women garment workers as well as their livelihood pattern. Three garment factories from Mirpur area under Dhaka district were selected purposively. The sample consisted of 90 women workers taking 30 randomly from each of the three garment factories. Data were collected through personal interviews with the selected samples. It was found that most of the respondents migrated to Dhaka because of their extreme poverty or insolvency. Few respondents had brought positive changes in their financial capital, decision marking and empowerment etc. The study revealed that 63.33 percent respondent's livelihood pattern has improved after involving in garment factory. Some diseases like eye trouble, headache, ear ache etc to be more prevalent among the women garment workers due to their involvement in garment factories. Incidence of physical weakness among the garment workers was very high. Women are exploited easily due to lack of technical knowledge and training. The employers do not pay any heed to this exploitation. Key words: Rural women; Urban garments; Livelihood; Garment workers DOI: 10.3329/jbau.v6i2.4846 J. Bangladesh Agril. Univ. 6(2): 449-456, 2008